THE THREE PILLARS OF TURKISH POLICY IN AFRICA - V. S. Iag’ia; M. A. Kolesnikova (Сравнительная политика)
Turkey as a new player in Africa has appeared with the collapse of  the bipolar system. Having proclaimed to build a multi-vector policy,  Ankara consistently implements the set strategy, which has the character of a comprehensive and long-term program and involves the intensifi cation of cooperation with African countries in the political, economic and humanitarian spheres. Turkey systematically promotes its political line in the region and has the  support of infl uential African elites in many countries of the  continent. At the same time the ruling Justice and Development  Party, helping to strengthen the economic positions of Turkish businessmen abroad, successfully copes with resolving problems of domestic policy by increasing the export of Turkish goods, spreading the idea of «moderate Islam» on the whole continent. Projects in the humanitarian field that are  implemented by the Turkish government and nongovernmental organizations are also successful. However, there  are series of tactical complexities associated with the aggravation of  the previous and the emergence of new problems caused by various  factors of political, economic and ideological origins. Nevertheless,  Ankara is suggested to continue its attempts to conduct an active policy aimed at the conquest of regional leadership and strengthening its presence in Africa in the future.